2014
DOI: 10.1371/journal.pone.0103531
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Ventilation for Comatose Patients with Inoperative Acute Intracerebral Hemorrhage: Possible Futility of Treatment

Abstract: BackgroundComatose patients with acute intracerebral hemorrhage (ICH) diagnosed as inoperative due to their severe comorbidity will be treated differently between countries. In certain countries including Japan, aggressive medical care may be performed according to the patients' family requests although the effects on the outcome are obscure. For respiratory distress in comatose patients with inoperative acute ICH, the role of mechanical ventilation on the outcome is unknown. We speculated that the efficacy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Similarly, Fugate[ 19 ] also believe that preoperative GCS score could not predict the patient’s outcome because the intervention of surgical operation could affect the outcome, which could be good recovery, severe disability or even death. It has been reported that mechanical ventilation treatment in the comatose patients resulting from inoperative acute intracerebral hemorrhage, especially patients had brainstem compression due to brain herniation, could only prolong unresponsive life[ 20 ]. Brainstem compression causes changes in respiratory rhythm and even respiratory arrest, it is the second reason (24.3%) in this study for the patients required mechanical ventilation and majority of them (85.2%) died.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Fugate[ 19 ] also believe that preoperative GCS score could not predict the patient’s outcome because the intervention of surgical operation could affect the outcome, which could be good recovery, severe disability or even death. It has been reported that mechanical ventilation treatment in the comatose patients resulting from inoperative acute intracerebral hemorrhage, especially patients had brainstem compression due to brain herniation, could only prolong unresponsive life[ 20 ]. Brainstem compression causes changes in respiratory rhythm and even respiratory arrest, it is the second reason (24.3%) in this study for the patients required mechanical ventilation and majority of them (85.2%) died.…”
Section: Discussionmentioning
confidence: 99%
“…Their purpose is to provide help in solving ethically complex situations and to give recommendations about managing certain cases (11). Based on the objective medical factors, a good assessment of treatment outcomes can be made and further medical procedures directed (13). Likewise, decision-making about further treatment should always take into account patients' quality of life (10).…”
Section: Discussionmentioning
confidence: 99%
“…This does not necessarily mean that the sICH incidence in the DPC database is unreliable, since the mortality is a different parameter from the incidence, as shown in Figure 1 . The mortality due to sICH was reported to be lower in Japan than in any other region [ 1 ], and this might result from an intensive medical intervention attitude even for comatose patients with sICH [ 12 ]. Further, we should be skeptical about the accuracy of the reported mortality number, since this also definitely contains errors due to misdiagnosis [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%